The future of the ASEAN regional forum - Desker, Barry (2016)
My attention to this issue was prompted by recent reports that the George W. Bush Administration is re-thinking its relationship to the main regional groupings – ASEAN, the ARF and APEC – as part of a larger review of US Policy in the Asia-Pacific region. These regional groupings are regarded as ‘talk shops’ with little substance and containing states with disparate beliefs and outlooks. ASEAN’s leading role in these institutions is questioned as the ASEAN region continues to be mired in economic crisis.